Editorial - Anna Oksiutycz (Communicare)
This issue marks three years of Communicare: Journal for Communication Studies in Africa publishing in an open-access format under UJ Press. Since 2022, the journal has achieved significant milestones by retaining South Africa's Department of Higher Education accreditation and being added to the Directory of Open Access Journals (DOAJ) in 2024. Communicare is a top performing among UJ Press journals with monthly views between 1500 and 3000. These successes are attributed to the contributions of editors, reviewers, authors, readers and the production staff.